2011
DOI: 10.1007/s00784-011-0649-1
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding incidence after oral surgery with continued oral anticoagulation

Abstract: The results suggest that oral surgical procedures can be performed safely without alteration of the oral anticoagulant treatment. CINICAL RELEVANCE: Local hemostasis with collagen fleece, local flap, and acrylic splint seems to be sufficient to prevent postoperative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 38 publications
2
26
0
5
Order By: Relevance
“…Results from several studies have shown that minor dentoalveolar surgery can be performed safely without interruption of OAT in patients who are therapeutically anticoagulated. [5][6][7][8][9][10][11][12][13][14][15][16] However, there is a lack of evidence concerning the safety of high-risk dentoalveolar surgery in patients who continued using OAT, as well as about the safety of dentoalveolar surgery in patients who are highly anticoagulated. 15 van Diermen and colleagues 21 recommended discussion with the patient's physician if the patient's INR is higher than 3.5 and if more complicated or invasive surgical procedures are planned (level of evidence A, recommendation class I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from several studies have shown that minor dentoalveolar surgery can be performed safely without interruption of OAT in patients who are therapeutically anticoagulated. [5][6][7][8][9][10][11][12][13][14][15][16] However, there is a lack of evidence concerning the safety of high-risk dentoalveolar surgery in patients who continued using OAT, as well as about the safety of dentoalveolar surgery in patients who are highly anticoagulated. 15 van Diermen and colleagues 21 recommended discussion with the patient's physician if the patient's INR is higher than 3.5 and if more complicated or invasive surgical procedures are planned (level of evidence A, recommendation class I).…”
Section: Discussionmentioning
confidence: 99%
“…5 Results from numerous reports show that dental extractions can be performed safely in patients receiving OAT if INR values are in the therapeutic range (< 4.0), providing that efficient local hemostatic measures are used. [5][6][7][8][9][10][11][12][13][14][15][16] The most commonly used local hemostatic agents are absorbable gelatin or collagen sponges, oxidized regenerated cellulose, fibrin glue, and antifibrinolytics applied directly into the wound or in the form of a solution as a mouthwash.…”
mentioning
confidence: 99%
“…Most of the studies published in the current literature primarily focused on tooth extraction. Data about extended oral surgical procedures such as implant dentistry and augmentation procedures (Bacci et al 2011;Gomez-Moreno et al 2015), cystic excisions (Sacco et al 2007), mucoperiosteal flaps (Campbell et al 2000), osteotomies and abscess incisions (Bublitz et al 2000;Eichhorn et al 2012;Kammerer et al 2015) are rare. For clinical practice, it would be useful to categorize dental surgical procedures by their invasiveness and assess the related risk of a postoperative bleeding to give treatment-based recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Les analyses multivariées ont été réalisées à l'aide de régression logistique. [11,14]. En réalité, il semble qu'une interruption brève du traitement par le patient ne s'accompagne que rarement d'événements thromboemboliques [18].…”
Section: Méthode Statistiqueunclassified